IMPLEMENTING GLOBAL PUBLIC INTEREST IN INFORMATION SOCIETY - Jakhu, Ram (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
Because the means of communication through which information is conveyed are indispensable for the eradication of poverty, public interest requires that all information and communications technology services must be available at affordable cost in all countries and to all areas within a country. Unfortunately, in spite of numerous international efforts, a digital divide still exists at both the national and international levels. Bridging this divide will be extremely difficult in the near future if the international and national regulatory regimes and approaches applicable to means of communications are not revised. There are many challenges, including access to appropriate national communication facilities, the privatisation of international operators in the field of satellite communications, the provision of domestic services by foreign operators, and the lack of national regulatory frameworks. To improve the situation, the Tunis Phase of the WSIS should ensure that all States and relevant international organisations follow the results of the Summit, and should focus on increasing the human intellectual capacity in regulatory matters.